FATHONAH ATTITUDES IN LYRICS OF CAT STEVENS ALBUM "TEASER AND THE FIRECAT" - Mizar Chumayun; Winantu Kurnianingtyas Sri Agung (ANGLO-SAXON: Jurnal Ilmiah Program Studi Pendidikan Bahasa Inggris, 2022)
This article investigates fathonah attitudes in the song lyrics of Cat Stevens album â€œTeaser and the Firecatâ€. The researcher used library research which applied descriptive approach. The primary data sources were the song lyrics of Cat Stevens album â€œTeaser and the Firecatâ€. For collecting the data, the researcher used documentation technique. Furthermore, content analysis were used to analyze the data. The results of the research showed that there are 22 fathonah attitudes contained in the song lyrics of Cat Stevens album â€œTeaser and the Firecatâ€ and categorized based on three types, namely intellectual, spiritual, and emotional. Therefore, the results of this study is expected to give many benefits for music world so that the world of music can create a song that can be used for teaching materials. For the researcher, this research also increase the understanding in interpreting Cat Stevensâ€™s album â€œTeaser and the Firecatâ€. Furthermore, the readers or future researchers can use Cat Stevensâ€™s album â€œTeaser and the Firecatâ€ as a source of information to find out the moral message so that it can be an afterthought in life and to motivate other people to do something good.Â